Nodal Discontinuous Galerkin Methods Algorithms, Analysis, and Applications - Hesthaven, Jan S.; Warburton, Tim.; SpringerLink (Online service) (New York, NY : Springer New York, 2008)
This book discusses a family of computational methods, known as discontinuous Galerkin methods, for solving partial differential equations. While these methods have been known since the early 1970s, they have experienced an almost explosive growth interest during the last ten to fifteen years, leading both to substantial theoretical developments and the application of these methods to a broad range of problems. These methods are different in nature from standard methods such as finite element or finite difference methods, often presenting a challenge in the transition from theoretical developments to actual implementations and applications. This book is aimed at graduate level classes in applied and computational mathematics. The combination of an in depth discussion of the fundamental properties of the discontinuous Galerkin computational methods with the availability of extensive software allows students to gain first hand experience from the beginning without eliminating theoretical insight. Jan S. Hesthaven is a professor of Applied Mathematics at Brown University. Tim Warburton is an assistant professor of Applied and Computational Mathematics at Rice University.
The key ideas -- Making it work in one dimension -- Insight through theory -- Nonlinear problems -- Beyond one dimension -- Higher-order equations -- Spectral properties of discontinuous Galerkin operators -- Curvilinear elements and nonconforming discretizations -- Into the third dimension.
Keywords: Mathematics; Partial differential equations; Numerical analysis; Physics; Computational intelligence; Mathematics; Numerical Analysis; Computational Intelligence; Mathematical Methods in Physics; Partial Differential Equations; Electronic books